Factors Predicting Frailty Among Postoperative Brain Tumor Patients - Mungngam C. (2023)
BACKGROUND: Surgical frailty is a condition in which patients are weak with varied recovery of various organ functions after surgery resulting in unpleasant outcomes. Frailty studies have been conducted in several populations with a limited knowledge on postoperative brain tumor patients. This study aimed to examine factors predicting frailty in brain tumor patients after craniotomy. METHODS: This study was a cross-sectional predictive study. The sample included 85 patients who were 18 years or older and underwent craniotomy with tumor removal from 1 university hospital in Bangkok, Thailand, between February and October 2021. Data were analyzed using descriptive statistic, Pearson correlation, and multiple linear regression, which determined significance level at.05. RESULTS: The prevalence of frailty among participants was 50.6%. Postoperative symptom and mood state were positively associated with frailty (r = 0.410 and r = 0.448, respectively; P <.01). Postoperative symptom, mood state, age, tumor type, and income could explain the variance of frailty in brain tumor patients after craniotomy by 40.3% (R2 = 0.403, P <.01). CONCLUSION: Healthcare providers should plan for discharge planning including assessment and develop the intervention for managing postoperative symptoms and psychological symptoms to promote recovery from frailty that generally occurs after brain tumor surgery.